The Relationship Between Self-Control and Bullying Behavior in Students - Wella, Prana; Dianto, Mori; Triyono, Triyono (Holistic Science, 2024)
This research is motivated by the phenomenon of many students who tend to behave in bullying ways such as cursing, hitting, throwing, calling names with labels, threatening, and scaring. Bullying behavior is a negative behavior that is suspected to be one of the causal factors of low self-control. The objectives of this study are to: 1) Describe student self-control, 2) Describe student behavior, 3) Test the relationship between self-control and bullying behavior. This type of research uses a quantitative descriptive approach with a correlational method. The population of this study was all students of class XI Phase F at SMA Negeri 2 Bukittinggi totaling 349 people with a research sample of 70 people using a purposive sampling technique. The instrument used was a questionnaire. Data analysis was processed using the product moment formula with Statistical Product and Service solution (SPSS) version 22. The results of this study revealed that, 1) Students' self-control is in the very good category 85.71%, 2) Students' bullying behavior is in the fairly high category 67.14%, 3) There is a relationship between self-control and bullying behavior of 0.235 with a strong correlation. This can be interpreted that the higher the students' self-control, the less bullying behavior in students.